Exploring the Experiences of Breastfeeding Women Whose Partners are Fly-in, Fly-out in Perth Western Australia - Critchett, Siana (Curtin University, 2021)
Fly-in, fly-out employment remains prevalent in Western Australia, however to date, no research has been conducted into the impacts of a FIFO lifestyle on breastfeeding. This study aimed to gain insight from women who were breastfeeding whilst their partners worked a FIFO roster, to better understand their supports, enablers, and barriers to continuing breastfeeding, with an aim to inform future support of families and health professionals in this area.